Kinetic Modelling of Molybdenum-blue Production by Bacillus sp. strain Neni-10 - Yakasai, M.H.; Manogaran, Motharasan (Journal of Environmental Microbiology and Toxicology, 2020)
Kinetic modelling of bacterial reduction process reveals vital parameters like specific reduction rate, hypothetical maximum reduction and deduce whether high substrate (molybdenum) concentration affects the lag phase of the reduction. The commonly used natural logarithmic transformation to linearize the reduction process seems inaccurate as it gives only an approximate value for the specific growth rate. This work for the first time utilized eight different primary models such as Gompertz, Baranyi-Roberts, Logistic, Von Bertalanffy, Richards, Schnute, Buchanan three-phase Huang to obtain values of the kinetic constants that could further be used for secondary modelling. Baranyi-Roberts model was the best model fitting Mo-blue production curve in Bacillus sp. strain Neni-10 based on statistical values for RMSE (root-mean-square error), R2 (adjusted coefficient of determination), AICc (corrected Akaike Information Criterion) BF (bias factor) and AF (accuracy factor). The fitting parameters obtained were lag time (l), maximal Mo-blue production (Ymax) and maximum Mo-blue production rate (mm). The use of microbial growth models to get accurate Mo-blue production rate is entirely new to molybdenum reduction (detoxification) process and the kinetic constants obtained could be very useful secondary modelling. This work has revealed the usefulness of these models in modelling bacterial Mo-blue production